1995
DOI: 10.1017/s0956796800001398
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping a parallel vision system in Standard ML

Abstract: The construction of a parallel vision system from Standard ML prototypes is presented. The system recognises 3D objects from 2D scenes through edge detection, grouping of edges into straight lines and line junction based model matching. Functional prototyping for parallelism is illustrated through the development of the straight line detection component. The assemblage of the whole system from prototyped components is then considered and its performance discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In short, the application should be portable across a variety of parallel architectures and indeed generations of the same parallel architecture where conventionally a upgrade would mean a new tuning phase. This moves forward from existing approaches, such as that of Michaelson and Scaife [3] who prototyped image processing systems in sequential ML but ported to and parallelised with occam. Here the parallelisation forms such an integral part of the prototyping process, that it can be abstracted in a flexible functional manner and re-used composably.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the application should be portable across a variety of parallel architectures and indeed generations of the same parallel architecture where conventionally a upgrade would mean a new tuning phase. This moves forward from existing approaches, such as that of Michaelson and Scaife [3] who prototyped image processing systems in sequential ML but ported to and parallelised with occam. Here the parallelisation forms such an integral part of the prototyping process, that it can be abstracted in a flexible functional manner and re-used composably.…”
Section: Discussionmentioning
confidence: 99%
“…From previous work [9,3] we have identified a small set of useful HOFs for which we have efficient parallel implementations. These are:…”
Section: A Standard Set Of Higher Order Functionsmentioning
confidence: 99%
“…We give brief examples of each algorithm in SML using the higher order function constructs that we have indicated can be implemented in parallel. Although we do not explicitly state, for each example, how the parallel implementation is derived from the prototype, we have substantial experience in this process [9,11] using 0ccam2 as the target language based on a Meiko transputer surface. We have shown that if we can write a functional language program using our standard set of higher order functions then we can develop an equivalent parallel implementation based on the parallel constructs for these functions.…”
Section: Fun Filter P [] = [] Imentioning
confidence: 99%
See 1 more Smart Citation
“…We are partly motivated by a research project 1 in which a parallelizing compiler for Standard ML (SML) is being developed. This project builds directly upon previous work on the development of parallel systems from functional prototypes (Michaelson and Scaife, 1995). Transformation rules for SML will play an important part within the compilation process.…”
Section: Introduction and Motivationsmentioning
confidence: 99%